2017
DOI: 10.1530/rep-17-0018
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, energy balance and spermatogenesis

Abstract: Obesity has grown to pandemic proportions. It affects an increasing number of children, adolescents and young adults exposed to the silent comorbidities of this disorder for a longer period. Infertility has arisen as one important comorbidity associated with the energy dysfunction promoted by obesity. Spermatogenesis is a highly regulated process that is determined by specific energetic requirements. The reproductive potential of males relies on hormonal-dependent and -independent stimuli that control sperm qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 104 publications
1
57
0
5
Order By: Relevance
“…Obesity is linked to several comorbidities, spanning from psychological, to mechanical and most particularly to metabolic disorders, leading to female and male gonadal dysfunction in addition to the well‐recognized increased risk for type 2 diabetes mellitus, dyslipidaemia, hypertension, cardiovascular disorders, and even some types of cancer . Moreover, as the number of children and young adults with obesity steadily increases, so does the prevalence of silent consequences resulting from the chronic metabolic imbalance, which will eventually lead to serious negative health impacts in the near future . One of the silent, yet most relevant consequences of obesity installed in early ages is the impairment of female and male reproductive function.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is linked to several comorbidities, spanning from psychological, to mechanical and most particularly to metabolic disorders, leading to female and male gonadal dysfunction in addition to the well‐recognized increased risk for type 2 diabetes mellitus, dyslipidaemia, hypertension, cardiovascular disorders, and even some types of cancer . Moreover, as the number of children and young adults with obesity steadily increases, so does the prevalence of silent consequences resulting from the chronic metabolic imbalance, which will eventually lead to serious negative health impacts in the near future . One of the silent, yet most relevant consequences of obesity installed in early ages is the impairment of female and male reproductive function.…”
Section: Introductionmentioning
confidence: 99%
“…Among metabolic disorders, overweight and obesity come irrecusably to the fore. Obese men suffer from different pathological and clinical conditions compromising spermatogenesis mainly due to the dysfunction of hypothalamic-pituitary-testis axis dysfunction which clearly links obesity to reduced fertility [5]. …”
Section: Introductionmentioning
confidence: 99%
“…However, modern diet seems to be increasingly making the body obese. Obesity is considered to be a very important health threat, it is accepted without obligation, but the obesity population is steadily increasing [1,2]. Obesity is not only closely related to various diseases and cancers but also affects quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore college students, in the early days of an adult, correct body shape management is essential for a healthy family [3]. Recent research has suggested that obesity is kind of a stigmatized condition [1,2]. Concerns with personal inferiority (social level), shame and self-criticism may impact on body shape management behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation